Sufficiency exam from the perspective of accounting sciences course students - Ribeiro, Sílvio Paula; Tisott, Sirlei Tonello; Santos, Cleston Alexandre dos; Carvalho, Denise dos Santos Silva de; Dias, Gabriela Carolina Ferreira (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: Analyze students' perceptions regarding the Accounting Science Proficiency Exam (ASE), as a way of ensuring a minimum level of competence to work in the job market. Methodology: Quantitative research, with data collected through an adapted and expanded questionnaire, based on Silva et al. (2020). The questionnaire was applied to 118 students from two educational institutions, located in a city in the interior of the state of Mato Grosso do Sul. Results: The analysis revealed that six variables stand out when emphasizing the appreciation of the accounting profession, the recognition of accounting professionals, the importance of the exam to improve the quality of the profession, the commitment and dedication of students in obtaining their diploma in the Accounting Sciences Course and in the ASE, in addition to the need for students to establish a study routine in order to pass the exam. The exploratory factor analysis allowed the classification of students' perceptions in relation to the ASE into four components, which explain 65.95% of the total variance. It is worth mentioning that the components that group the students' perceptions are linked to the job market, the approach to the content of the exam in the classroom, quality indicators and job opportunities for accounting professionals. In this regard, students demonstrated that they were aware of the importance of their respective participation in the teaching-learning process, recognizing that achieving their own educational objectives and entering the job market depends on their own commitment. Contributions of the Study: The study contributes theoretically to discussions around the ASE, which is fundamental for strengthening the accounting profession. It also highlights the importance of teachers and course coordinators being aware of the questions and materials of the most recent exams, as a way of adequately preparing students.